2013
DOI: 10.1007/s00104-013-2675-9
|View full text |Cite
|
Sign up to set email alerts
|

Erste Erfahrungen mit einem ERAS-Protokoll in der Ösophaguschirurgie

Abstract: HintergrundDie Prinzipien der multidisziplinären Rehabilitation nach chirurgischen Eingriffen (ERAS, "enhanced recovery after surgery") konnten bereits in der kolorektalen Chirurgie positive Effekte auf die Komplikationsraten

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The number of laboratory diagnostic items reduced, which could be due to the reduced postoperative complications, the standardized clinical pathway, the postoperative nursing care, and the combination of all measures in ERAS. [ 24 – 26 ] However, our findings suggested that anesthesia and operating room cost was similar in 2 groups. According to the previous studies, anesthesia and operating room cost was responsible for the second main absolute gain (£ 2045) in the ERAS group, which was in line with Labgaa's results.…”
Section: Discussionmentioning
confidence: 70%
“…The number of laboratory diagnostic items reduced, which could be due to the reduced postoperative complications, the standardized clinical pathway, the postoperative nursing care, and the combination of all measures in ERAS. [ 24 – 26 ] However, our findings suggested that anesthesia and operating room cost was similar in 2 groups. According to the previous studies, anesthesia and operating room cost was responsible for the second main absolute gain (£ 2045) in the ERAS group, which was in line with Labgaa's results.…”
Section: Discussionmentioning
confidence: 70%